RESILIENSI PEREMPUAN LAJANG DALAM METROPOP GANJIL-GENAP KARYA ALMIRA BASTARI - Intan, Tania (Sunan Kalijaga State Islamic University Yogyakarta, 2020)
In the context of Eastern culture, society views single women and men unequally. The demand for immediate marriage in women is greater than that of men. This research was conducted to reveal the resilience of single women represented by the protagonist of the novel Ganjil-Genap (2020) by Almira Bastari. The method used in this research is descriptive-qualitative. Data in the form of words, phrases, and sentences were collected using the listening technique and notes through closed reading. The data are then classified, interpreted, and then analyzed using feminist literary criticism. The theoretical foundation in this research comes from the ideas of Hurlock and Schoon. The results showed that (1) The institution of marriage is still coveted by independent, well-established, and logical female figures because singleness is a social category that is considered problematic. (2) In exercising resilience, women go through the overcoming, steering through, bouncing back, and reaching out stages. (3) The achievement that the female character produces from resilience is turning her position from object to subject.